Strategi Customer Relations BMW Eurokars sebagai Luxury Automotive Brand dalam Membangun Eksklusivitas dan Mempertahankan Loyal Customer - Amanda Putri Fakhrana; Burhanuddin Burhanuddin; Al-May Abyan Izzy Burhani (Journal of Creative Student Research, 2026)
The luxury automotive industry emphasizes not only product quality, but also service experience and emotional relationships with customers as part of building a premium brand image. BMW Eurokars, as an official BMW dealer in Indonesia, builds exclusivity through customer relations strategies oriented toward personalized service, continuous communication, and premium customer experiences. This study aims to identify the forms of exclusivity developed by BMW Eurokars and the customer relations strategies used to maintain loyal customers. The study employed a descriptive qualitative approach with data collection techniques consisting of in-depth interviews, observation, documentation, and literature review. The results show that exclusivity is built through various premium services such as private events, fast lane service, personalized gifts, personal communication, and customer lounge facilities designed to provide comfort and special treatment for customers. Customer relations strategies are implemented through consistent two-way communication, responsive aftersales services, and a relational approach focused on customer needs and comfort. These forms of service are able to create emotional attachment, increase customers’ sense of appreciation, and strengthen customer loyalty toward BMW Eurokars. This study indicates that exclusivity and relationship quality are important factors in maintaining loyal customers in the luxury automotive industry.